1983
DOI: 10.1111/j.1600-0447.1983.tb06730.x
|View full text |Cite
|
Sign up to set email alerts
|

Lomest psychiatric case register: the statistical context required for planning

Abstract: Descriptive statistics derived from a psychiatric case register are presented. They may be useful for a more rational planning of new services, and provide a preliminary evaluation of the effects of the recent Act (1978) which has abolished large mental hospitals in Italy. Each component of the 1-year prevalence rates has been examined closely, and the results have indicated three main considerations: abolishing the large mental hospital does not abolish the long-stay patients still living in it, and these peo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1984
1984
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…The programmes covered a range of mental disorders including common mental disorders, 19 , 20 severe mental illness, 21 substance misuse 22 and a combination of mental disorders 23–25 . The treatment programmes were equally varied, ranging from: a national programme increasing access to psychological therapies in England; 19 a regional methadone treatment programme in China; 22 the nationwide integration of depression treatment into primary care in Chile; 20 a national financing system to increase access to mental health specialists in Australia; 26 district-level community mental health services in Italy; 24 , 25 and regional hospital-based services for people with severe mental illness such as schizophrenia or bipolar disorder in Denmark 21 . Only two of the studies, both government-commissioned reports, evaluated coverage as part of a wider programme evaluation including the effect on patient outcomes and programme costs 19 , 26 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The programmes covered a range of mental disorders including common mental disorders, 19 , 20 severe mental illness, 21 substance misuse 22 and a combination of mental disorders 23–25 . The treatment programmes were equally varied, ranging from: a national programme increasing access to psychological therapies in England; 19 a regional methadone treatment programme in China; 22 the nationwide integration of depression treatment into primary care in Chile; 20 a national financing system to increase access to mental health specialists in Australia; 26 district-level community mental health services in Italy; 24 , 25 and regional hospital-based services for people with severe mental illness such as schizophrenia or bipolar disorder in Denmark 21 . Only two of the studies, both government-commissioned reports, evaluated coverage as part of a wider programme evaluation including the effect on patient outcomes and programme costs 19 , 26 .…”
Section: Resultsmentioning
confidence: 99%
“…Five studies determined service utilization from routine patient data collected by the programme 19 , 22 , 24 , 25 . One of these 21 collated data collected by the programme to a national level in the Danish Psychiatric Central Register, a computerized register which includes information about all admissions to psychiatric wards and outpatient contacts 27 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effica-well but analogous to that of 496 ciousness of community care as an for Salford (12). The Arezzo rate is alternative to hospital admissions higher than others published by and long-term hospitalization has Italian Services: 271 for the Loalready been described by Pasama-mest register (13), 208 for Verona- (14) and 124 for Porto. gruaio (15).…”
Section: Cmhs Incidence Ratesmentioning
confidence: 88%
“…This seems to demonstrate that the organizational system of care, with the availability of staff and back-up facilities outside the hospital, and the general policy of the service, community or hospital oriented, has a profound influence on the hospitalization rates. Marinoni et al (1983) have suggested that the decrease in admissions which occurred in Italy after the Reform Law may be the &dquo;obvious effect of narrowing the bottle neck&dquo;: this is certainly the case in big cities, such as Rome and Naples. The provision of GHPW beds in Mantua is in line with the North Central Italy rate, but there is a relative bottle-neck compared to Cremona.…”
Section: Discussionmentioning
confidence: 99%